Design of Flapping Wing Aircraft based on Crank Chute Mechanism - Qi Li; Yu Cai; Xiansheng Huang; Bin Liu (Jixie chuandong)
Aiming at the problem of phase lag in flapping wing of traditional flapping wing aircraft，a kind of flapping wing aircraft driven by crank chute mechanism is designed，its modeling and simulation analysis are carried out，the prototype is made and the actual flight test is carried out. The mass of the prototype is 26 g，the wingspan is 340 mm，and the maximum beating frequency is 17 Hz. The crank chute mechanism is analyzed theoretically，and the kinematic equation of the mechanism is deduced； the kinematic simulation analysis of crank chute mechanism is carried out by using the SolidWorks software. The motion characteristics of flapping wing aircraft under different crank length and different flapping frequency are studied，and a suitable crank length is determined； the power consumption of flapping wing aircraft with different motor types and reduction ratios is tested，and a set of low-power power devices is determined. The results show that the crank chute mechanism can eliminate the phase lag between the wings and reduce the influence of lift imbalance on the fuselage； when the crank length is 4.5 mm，the up stroke angle and down stroke angle of the wing are 45° and -15°； the flapping wing aircraft can achieve stable flight in the air.